1984
DOI: 10.1099/00222615-17-2-129
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a gram-negative anaerobe isolated from men with non-gonococcal urethritis

Abstract: SUMMARY. A small, fastidious gram-negative anaerobe was isolated from men with non-gonococcal urethritis (NGU). The isolates are described as NGU-associated anaerobes because they were extremely rare in men with urethritis other than NGU, and in asymptomatic men. They showed twitching motility, had many polar pili and appeared to be a homogenous group culturally, morphologically and biochemically. None of the strains fermented or utilised carbohydrates or organic acids as sole sources of carbon for energy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The bacteria has also been reported to be present in amniotic fluid and the genital tract of humans (5)(6)(7)(8). In addition, C. ureolyticus has commonly been isolated from patients suffering from periodontal disease, a disease which involves inflammatory and destructive conditions of the tissues surrounding the teeth (6).…”
mentioning
confidence: 99%
“…The bacteria has also been reported to be present in amniotic fluid and the genital tract of humans (5)(6)(7)(8). In addition, C. ureolyticus has commonly been isolated from patients suffering from periodontal disease, a disease which involves inflammatory and destructive conditions of the tissues surrounding the teeth (6).…”
mentioning
confidence: 99%
“…ureolyticus (Fontaine et al 1986), which had been iso-lated from the urethra of men with NGU, and the type strain (NCTC 10941), were examined. The organisms were grown and maintained as described previously (Fontaine et al 1984).…”
Section: S T R a I N S A N D C U L T I V A T I O Nmentioning
confidence: 99%
“…Bacteroides ureolyticus, a urease-positive, obligately anaerobic organism, occurs frequently in lower genital-tract infections and is probably responsible for some cases of non-gonococcal urethritis (NGU) in men (Fontaine et al 1982;Hawkins et al 1988). It has also been isolated from necrotic or gangrenous lesions, perianal abscesses, soft tissue infections and ulcers and lesions of the lower limbs (Duerden et al 1982).…”
mentioning
confidence: 99%
“…It has been reported to be isolated in mixed cultures from infections of virtually every organ system in humans (22). In particular, it was previously thought to be associated with male nongonococcal urethritis (NGU) (12,14,17). Fontaine et al (14) reported the isolation of a gram-negative, non-spore-forming, anaerobic bacillus from 50% of men with NGU and 13% of men without disease.…”
mentioning
confidence: 99%